2007
DOI: 10.1097/01.sla.0000251747.80025.b7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis Is a Risk Factor for Postoperative Complications After Major Hepatectomy

Abstract: Steatosis per se is a risk factor for postoperative complications after major hepatectomy and should be considered in the planning of surgery. Caution must be taken to perform major hepatectomy in steatotic patients with preexisting cholestasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
4
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(247 citation statements)
references
References 36 publications
7
228
4
8
Order By: Relevance
“…The disease spectrum of NAFLD ranges from simple steatosis to nonalcoholic steatohepatitis (NASH), which can further progress into fibrosis, cirrhosis, and ultimately into endstage liver disease, posing a significant burden on liver transplantation waiting lists. Moreover, clinical studies identified severe macrovesicular steatosis (>66%) as an exclusion criterion for patients requiring major liver resection because of the concomitant high risk of postoperative complications (3,4). In living donor liver transplantation (LDLT) procedures steatosis is considered even more deleterious, posing a risk for both the donor and the recipient.…”
Section: Nonalcoholic Fatty Liver Disease (Nafld) Ismentioning
confidence: 99%
“…The disease spectrum of NAFLD ranges from simple steatosis to nonalcoholic steatohepatitis (NASH), which can further progress into fibrosis, cirrhosis, and ultimately into endstage liver disease, posing a significant burden on liver transplantation waiting lists. Moreover, clinical studies identified severe macrovesicular steatosis (>66%) as an exclusion criterion for patients requiring major liver resection because of the concomitant high risk of postoperative complications (3,4). In living donor liver transplantation (LDLT) procedures steatosis is considered even more deleterious, posing a risk for both the donor and the recipient.…”
Section: Nonalcoholic Fatty Liver Disease (Nafld) Ismentioning
confidence: 99%
“…The effect of hepatic steatosis on short term post operative outcomes has been widely investigated (9)(10)(11)(12)(13) . The general underlying theme in these studies seemed to indicate that patients with steatosis were susceptible to a more arduous post operative course with respect to complication rates and short term morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that steatohepatitis is associated with an increased mortality after hepatectomy and the use of Irinotecan should be carefully considered. Recent studies reported steatosis as an independent factor for morbidity and mortality rates in patients undergoing hepatectomy (10,11,12) . Considering the pathophysiology and risk factors for steatohepatitis, and in view of the evidence given above, it would appear that hepatic steatosis and obesity are relative contraindications in patients undergoing hepatectomy for CRLM.…”
Section: Introductionmentioning
confidence: 99%
“…Indication for blood transfusion was massive hemorrhage (> 1500 mL) within 24 to 48 hours after surgery. 10,11 All patients who developed postoperative hemorrhage underwent abdominal CT scans and were divided into 2 groups based on the CT findings. Patients who did not have contrast material extravasation were considered to have coagulopathic hemorrhage (n = 15), and patients who presented with extravasation of contrast material were considered to have noncoagulopathic hemorrhage (n = 17).…”
Section: Patients and Definitions Of Hemorrhage After Livingdonor LIVmentioning
confidence: 99%